Harvestmen in the first twenty years: a scientometric analysis of Zootaxa’s contribution to opilionology (Arthropoda, Arachnida, Opiliones) - Pérez-González, Abel; Acosta, Luis E.; Proud, Daniel N.; Shultz, Jeffrey W. (Zootaxa, 2021)
In its first twenty years of existence Zootaxa has been widely utilized among researchers of Opiliones, mainly those coming from Latin American countries, principally Brazil. During 2003–2020, a total of 141 papers on Opiliones were published in Zootaxa (no papers were published on Opiliones in the first two years, 2001–2002). The journal has greatly facilitated the dissemination of knowledge on Opiliones, especially with respect to the taxonomy and systematics of harvestmen from the Neotropical Realm. Those 141 papers in Zootaxa include almost a quarter (191) of the new species of Opiliones described between 2001 and 2020, as well as 112 new synonymies. Additionally, 27 of those papers proposed 182 new or restored combinations. A total of 108 authors working in 25 countries have contributed papers to Zootaxa focusing on Opiliones. There is clearly a predominance for collaborative contributions with more than twice as many papers authored by two or more authors compared to single-author publications. In general, the majority of papers deal within the local biogeographic realm (where the lead author resides). Studies of harvestmen from seven of the eight biogeographic realms were published in Zootaxa during 2003–2020. The largest portion of these contributions were by far focused on the Neotropical opiliofauna, but Australasian, Nearctic, Indomalayan, Palearctic, Afrotropical and Antarctic opiliofauna are covered as well. No papers on Opiliones have been published in Zootaxa by authors representing countries in Africa. We also recognize a strong gender bias in authorship and the current composition of Opiliones subject editors. We will strive to create an inclusive environment and aim to promote diversity of scientists who study Opiliones.